Additional professional education at humanities university - Irina M. Shadrina (Высшее образование в России)
The best practices in realizing the additional education programs at Murmansk State Humanities University are presented in the article. The authors reveal the peculiarities andtendencies of additional professional education development in the educational segment MSHU – university, putting an emphasis on the development of moral values of society and on its spiritual renewal.